Altered chromatin landscape and 3D interactions associated with primary constitutional MLH1 epimutations - Paula Climent-Cantó; Marc Subirana-Granés; Mireia Ramos-Rodríguez; Estela Dámaso; Fátima Marín; Covadonga Vara; Beatriz Pérez-González; Helena Raurell; Elisabet Munté; José Luis Soto; Ángel Alonso; GiWon Shin; et al. (Clinical Epigenetics)
Abstract Background Lynch syndrome (LS), characterised by an increased risk for cancer, is mainly caused by germline pathogenic variants affecting a mismatch repair gene (MLH1, MSH2, MSH6, PMS2). Occasionally, LS may be caused by constitutional MLH1 epimutation (CME) characterised by soma-wide methylation of one allele of the MLH1 promoter. Most of these are “primary” epimutations, arising de novo without any apparent underlying cis-genetic cause, and are reversible between generations. We aimed to characterise genetic and gene regulatory changes associated with primary CME to elucidate possible underlying molecular mechanisms. Methods Four carriers of a primary CME and three non-methylated relatives carrying the same genetic haplotype were included. Genetic alterations were sought using linked-read WGS in blood DNA. Transcriptome (RNA-seq), chromatin landscape (ATAC-seq, H3K27ac CUT&Tag) and 3D chromatin interactions (UMI-4C) were studied in lymphoblastoid cell lines. The MLH1 promoter SNP (c.-93G > A, rs1800734) was used as a reporter in heterozygotes to assess allele-specific chromatin conformation states. Results MLH1 epimutant alleles presented a closed chromatin conformation and decreased levels of H3K27ac, as compared to the unmethylated allele. Moreover, the epimutant MLH1 promoter exhibited differential 3D chromatin contacts, including lost and gained interactions with distal regulatory elements. Of note, rare genetic alterations potentially affecting transcription factor binding sites were found in the promoter-contacting region of CME carriers. Conclusions Primary CMEs present allele-specific differential interaction patterns with neighbouring genes and regulatory elements. The role of the identified cis-regulatory regions in the molecular mechanism underlying the origin and maintenance of CME requires further investigation.